2019
DOI: 10.17728/jaft.6464
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Properties of Buffalo skin Gelatin Extracted Using Crude Acid Protease from Cow’s Abomasum

Abstract: The study was investigated the functional properties of buffalo skin gelatine. Gelatine was extracted from swamp buffalo skin using crude acid protease from cow’s abomasum (CAPC) in concentration variation 0; 2.5; 5; and 7.5 U/mg. The temperature to hydrolysis included at 28 °C, 37°C and 40°C. The emulsion activity index (EAI), Emulsion stability index (ESI), foaming expansion (FE) and foaming stability (FS) were investigated. The interaction between CAPC concentration and hydrolysis temperature has a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 14 publications
2
17
1
Order By: Relevance
“…Whereas the foam stability for NE was (13.33 ± 1.15 %) and PE (13.00 ± 1.00 %) at 30 min, while at 60 min, PE (12.67 ± 1.53 %) and NE (11.33±0.58 %) showing no significant difference (p > 0.05). Mulyani et al (2019) reported a higher FE (102.93 %) and FS (44.91-55.00 %) value compared to the result of this study. The study by Khiari et al (2013), of enzymatically extracted fish gelatin, resulted in more stable foam as compared to NE due to high negatively charged amino acids in the gelatin.…”
Section: Foaming Capacity and Stabilitycontrasting
confidence: 76%
See 3 more Smart Citations
“…Whereas the foam stability for NE was (13.33 ± 1.15 %) and PE (13.00 ± 1.00 %) at 30 min, while at 60 min, PE (12.67 ± 1.53 %) and NE (11.33±0.58 %) showing no significant difference (p > 0.05). Mulyani et al (2019) reported a higher FE (102.93 %) and FS (44.91-55.00 %) value compared to the result of this study. The study by Khiari et al (2013), of enzymatically extracted fish gelatin, resulted in more stable foam as compared to NE due to high negatively charged amino acids in the gelatin.…”
Section: Foaming Capacity and Stabilitycontrasting
confidence: 76%
“…There was no significant difference observed for both samples (p > 0.05). The EAI value or NE was similar to gelatin extracted by Mulyani et al (2019) (12.03 m 2 /g). In contrast, PE was slightly lower as compared to Mulyani et al (2019) for gelatin extracted from buffalo skin.…”
Section: Emulsifying Property and Capacitysupporting
confidence: 57%
See 2 more Smart Citations
“…Gelatine is also used in confectionery due to its foaming ability, for example in marshmallow production [ 123 ]. Foaming increases with the amount of hydrophobic amino acids such as alanine, valine, isoleucine, leucine, proline, methionine, phenylalanine, tyrosine, and tryptophan, as hydrophobicity is a requirement for adsorption at the air–water interface [ 124 ].…”
Section: Proteinsmentioning
confidence: 99%